2016
DOI: 10.3892/ijmm.2016.2603
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of magnesium isoglycyrrhizinate in non-alcoholic fatty liver disease and the associated molecular mechanisms

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common liver diseases worldwide and there is an urgent need to identify effective pharmacological strategies to treat NAFLD. For this purpose, in the present study, we examined the the possible molecular mechanisms responsible for the effects of MgIG and the protective effects of MgIG in a model of NAFLD. The human hepatic L02 cell line and oleic acid were employed to establish an in vitro model of NAFLD. The CCK-8 assay, Hoechst 33258 staining and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…At present, the protective effects of MgIG on liver injury are mainly attributed to STAT3 (Zhao Z. et al, 2017), hedgehog (Lu et al, 2017), NF-κB signaling pathway (Xu et al, 2016; Jiang et al, 2017a; Zhao X.J. et al, 2017) and phospholipase A2/arachidonic acid pathway (Xie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the protective effects of MgIG on liver injury are mainly attributed to STAT3 (Zhao Z. et al, 2017), hedgehog (Lu et al, 2017), NF-κB signaling pathway (Xu et al, 2016; Jiang et al, 2017a; Zhao X.J. et al, 2017) and phospholipase A2/arachidonic acid pathway (Xie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The full name of MgiG is tetrahydrate magnesium 18α, 20β-hydroxy-11-oxon orolean-12-en-3β-yl-2-O-β-D-glucopyranurosyl-α-D-glucopy ranosiduronate ( 13 ). Previous studies have demonstrated that MgiG attenuates liver injury caused by toxins (carbon tetrachloride and D-galactosamine) and other factors, including free fatty acid, ethanol and ischemia/reperfusion ( 14 ). MgiG exerts a greater liver-protecting effect than glycyrrhizin or β-glycyrrhizic acid ( 15 - 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we further argued that while these cells seemed to activate the apoptotic machinery, the cells did not exhibit higher cell death compared to activated LX2 cells when subjected to the same concentrations of MgIG. Therefore, this led us to hypothesize that (1) either LO2 cells were indeed more resistant to MgIG-induced cytotoxicity than LX2 cells or (2) that MgIG might indeed have cell specific hepatoprotective effects on LO2 cells, the latter being more plausible due to the number of mechanistic studies supporting its protective effects on hepatocytes ( Zheng et al, 2015 ; Xu et al, 2016 ; Lu et al, 2017 ; Wu et al, 2018 ). In the context of liver fibrosis, as the injury persist, apoptotic hepatocytes may trigger the activation of HSCs and thus deteriorate the fibrotic condition ( Puche et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%